Selecting a Small Portfolio of Equities: One-stop Shopping Approach to Screening - Boďa, Martin; Kanderová, Mária (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Investing into equities requires that a pre-selection of candidate equities be made, which is frequently accomplished by means of a screening criterion such as market capitalization, a fundamental indicator of past performance. The paper considers four screening criteria – market capitalization, two multiples (the P/B and P/E ratios) and historical yield – and investigates how the pre-selection choice based on any of these criteria and orientation towards small/low or big/high poles of equity styles affects the performance of a small portfolio comprising 50 equities at most. The goal of the investigation undertaken in the paper is to assess usefulness of these distant poles of equity styles and evaluate their performance against trending patterns of the market. The method is experimental and in order to assure robustness of results it employs 5 consecutive four-year datasets from 2009 to 2016 and three conceptually different methods of portfolio selection, setting the S&P 500 Index as benchmark. The results indicate that superiority of equity styles and selection methods is contingent on market cycle: in bull markets with steady growth, equity styles with small/low polarity seem more dependable, but when market price patterns change between bull and bear markets, big/high poles seem guarantee better performance
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 43-58
Keywords: equity style; asset pre-selection; market capitalization; multiple; historical yield; performance